Adjustment of the hazen-willians equation for determination of continuous pressure drop in PVC pipe - Miranda, Eugenio Paceli; Custodio, Tatiana Belo De Sousa; DE LIMA, Francisco Uchoa; Pereira, Taiane Almenda; Bicudo, Andre Luiz Ribeiro [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
The head loss is a fundamental parameter for the dimensioning of the pipes, being directly related to the cost of these pipes, the selection of the pumping system and the energy cost of electricity. That study fitted the Hazen-Williams equation and compared it with the Darcy-Weisbach equation. The performance of the adjusted equation was determined by the concordance index (c), Statistical Standard Error (EPE) and Mean Absolute Error (EAM). The results show that all gridded indices to verify the performance of the adjusted Hazen-Willians equation have improved. The largest difference between the values of continuous load loss. between the Darcy-Weisbach method and the adjusted Hazen-Williams equation was about 0.08%, which can be considered extremely low.
Ajuste da equação de hazen-willians para determinação da perda de carga contínua em tubulações de PVC
Keywords: Darcy-Weisbach; Diameter; Head loss